Cobalt Encapsulated in Nitrogen-Doped Graphite-like Shells as Efficient Catalyst for Selective Oxidation of Arylalkanes - Shuo Li; Shafqat Ali; Zareen Zuhra; Huahuai Shen; Jiaxiang Qiu; Yanbin Zeng; Ke Zheng; Xiaoxia Wang; Guanqun Xie; Shujiang Ding (Molecules, 2023)
Selective oxidation of ethylbenzene to acetophenne is an important process in both organic synthesis and fine chemicals diligence. The cobalt-based catalysts combined with nitrogen-doped carbon have received great attention in ethylbenzene (EB) oxidation. Here, a series of cobalt catalysts with metallic cobalt nanoparticles (NPs) encapsulated in nitrogen-doped graphite-like carbon shells (Co@NC) have been constructed through the one-pot pyrolysis method in the presence of different nitrogen-containing compounds (urea, dicyandiamide and melamine), and their catalytic performance in solvent-free oxidation of EB with tert-butyl hydrogen peroxide (TBHP) as an oxidant was investigated. Under optimized conditions, the UCo@NC (urea as nitrogen source) could afford 95.2% conversion of EB and 96.0% selectivity to acetophenone, and the substrate scalability was remarkable. Kinetics show that UCo@NC contributes to EB oxidation with an apparent activation energy of 32.3 kJ/mol. The synergistic effect between metallic cobalt NPs and nitrogen-doped graphite-like carbon layers was obviously observed and, especially, the graphitic N species plays a key role during the oxidation reaction. The structure–performance relationship illustrated that EB oxidation was a free radical reaction through 1-phenylethanol as an intermediate, and the possible reaction mechanistic has been proposed.